Illuminating the sunbeam through glass motif. Issue 4 (2nd October 2022) - Hutterer, Maile s.
Abstract: In the Middle Ages, the image of a sunbeam passing through glass or crystal was a popular metaphor for explaining Mary's perpetual virginity. One of the most frequently repeated quotations that employs this metaphor has long been attributed to the twelfth-century Cistercian abbot St Bernard of Clairvaux, which might suggest that the emergent Gothic style contributed to its contemporaneous propagation in text and image. However, this much-repeated quotation is in fact the commentary of a seventeenth-century Dominican scholar, who mixed a widespread medieval trope with Bernard's own discourse. A reevaluation of the use of the sunbeam motif in text and image suggests that, whereas it was commonly used to explain the Virgin Birth in literature, in visual art it was more frequently associated with the Incarnation. Furthermore, as I argue, the translation of the motif from text to image appears to have been catalyzed by a materially focused affective piety and the devotional texts of late medieval mystics such as the Meditationes vitae Christi and St Bridget of Sweden's Revelations .